Prevalence of Dental Anomalies among Iraqi Dental Students - Areej A. Najm; Alaa Salah Mahdi; Resha J. Al-Sudani; Hanadi Hekmat Musa (College of Dentistry/ University of Baghdad, 2016)
Background: Dental anomalies are abnormal tooth condition occurs due to certain genes or environmental factor disturb tooth development during morphodifferentiation stages, affecting group of teeth or entire dentition. The aim of the study is to evaluate the frequency of occurrence of dental anomalies among dental student. Materials and Methods: Three hundred dental students with age ranged (18-23 years) were examined clinically and radiographically searching for dental anomalies in shape, number and position. Results: Only 25 students (8.3 %) from the total sample (300) had dental anomalies, female form the higher percentage of anomalies (about 68%) compared to male (32%). The age group (22 years) which was the larger group had a higher percentage of dental anomalies (about 40%). Regarding the type of anomalies found, disturbance in number of teeth represent the higher percentage (48%); but impacted third molar represent the most common subtype of positional anomalies found in the study (20%). Conclusion: Higher percentage of dental anomalies detected in female and larger age group, study of dental anomalies was of great importance especially prior to orthodontic and surgical intervention.